Achieving efficient routing in constrained networks with unidirectional links through Software Defined Networking. - Alves, Renan Cerqueira Afonso (2020)
Wireless Sensor Networks are composed of constrained devices subjected to low energy budget, limited processing capability, and reduced memory availability. A wireless communication link between two devices may become unidirectional due to transmission power disparity, non-isotropic antennas, or device heterogeneity; using such links holds the potential to shorten communication routes, saving resources. Our objective is to design a set of protocols that enable routing in a network with unidirectional links, while attending the requirements imposed by the limited resources available. We used the Software Defined Networking paradigm to solve this challenge, as the centralized control enables calculating routes with unidirectional links in a general fashion without relying on flooding-based techniques. We designed the underlying Neighbor Discovery and Controller algorithms required by Software Defined Wireless Sensor Networks. First we designed simple discovery algorithms to demonstrate the feasibility of our approach; next, we provided enhanced discovery algorithms that dealt with scalability issues. We executed experiments to check the occurrence of unidirectional links in a testbed, and implemented and tested our algorithms in a simulated/emulated environment. The discovery algorithms were tested on networks containing from 16 to 100 nodes, deployed randomly or as a grid. Each topology was tested in four link configurations: bidirectional links only, randomly selected unidirectional links, randomly selected nodes with increased range, and unidirectional links from the network controller to all other nodes. As a baseline, we considered a standard discovery algorithm used in Software Defined Wireless Sensor Networks, the Collect-based discovery. Employing unidirectional links yielded at least 90% packet delivered, whereas the Collectbased discovery yielded less 50% delivery on most cases, considering our experiments on topologies with unidirectional links. The final contribution is an asynchronous Radio Duty Cycling algorithm, to the best of our knowledge, the first to work under unidirectional links. When Radio Duty Cycling is present, the analysis showed that using unidirectional links is beneficial mostly in scenarios with long-reaching links.